2012
DOI: 10.24846/v21i2y201203
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Bee Colony (ABC) Algorithm for Constrained Optimization Improved with Genetic Operators

Abstract: Artificial bee colony (ABC) is a relatively new swarm intelligence based metaheuristic. It was successfully applied to unconstrained optimization problems and later it was adjusted for constrained problems as well. In this paper we introduce modifications to the ABC algorithm for constrained optimization problems that improve performance of the algorithm. Modifications are based on genetic algorithm (GA) operators and are applied to the creation of new candidate solutions. We implemented our modified algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 16 publications
(26 reference statements)
0
47
0
2
Order By: Relevance
“…In addition, smart flight operator is employed to be used in scout bee instead of the random selection mechanism in original ABC. The numerical results showed that M-ABC provides comparable results with respect to algorithms under comparison [19].…”
Section: Constrained Artificial Bee Colonymentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, smart flight operator is employed to be used in scout bee instead of the random selection mechanism in original ABC. The numerical results showed that M-ABC provides comparable results with respect to algorithms under comparison [19].…”
Section: Constrained Artificial Bee Colonymentioning
confidence: 58%
“…Mezura-Montes and Cetina-Domínguez [19] presented a modified ABC (M-ABC). Compared with the original constrained ABC four modifications on the selection mechanism, the equality and boundary constraints, and scout bee operators are presented.…”
Section: Constrained Artificial Bee Colonymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the convergence of the modeling error to zero can be achieved by the optimization of the parameters of several parameters of the fuzzy models including input membership functions or parameters in the rule consequents. Various optimization algorithms can be implemented in this context [28], [29], [30], [31], [32], [33], [34], [35], [36]. …”
Section: Resultsmentioning
confidence: 99%
“…Meta-sezgisel algoritmaların orijinal versiyonları, çözüm kalitesini artırmak için modifiye edilir veya melezleştirilir. En yaygın doğadan esinlenen algoritmalar, parçacık sürü optimizasyonu (PSO) [18], diferansiyel evrim (DE) [19], ateşböceği algoritması (FA) [20], [21], guguk kuşu arama (CS) [22], karınca koloni optimizasyonu [23][24][25][26], yapay arı koloni algoritması [27][28][29][30], yarasa algoritması (BA) [31], ağaç tohum algoritması [32] …”
Section: Gi̇ri̇ş (Introduction)unclassified